2008
DOI: 10.1073/pnas.0800406105
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution mass spectrometry of viral assemblies: Molecular composition and stability of dimorphic hepatitis B virus capsids

Abstract: Hepatitis B virus (HBV) is a major human pathogen. In addition to its importance in human health, there is growing interest in adapting HBV and other viruses for drug delivery and other nanotechnological applications. In both contexts, precise biophysical characterization of these large macromolecular particles is fundamental. HBV capsids are unusual in that they exhibit two distinct icosahedral geometries, nominally composed of 90 and 120 dimers with masses of Ϸ3 and Ϸ4 MDa, respectively. Here, a mass spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
206
1
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 200 publications
(224 citation statements)
references
References 43 publications
8
206
1
3
Order By: Relevance
“…This process can occur repeatedly, limited by the absolute number of charges and activation energy available [49]. Indeed, in favorable cases as many as seven successive dissociation steps have been observed [50].…”
Section: Collision-induced Dissociationmentioning
confidence: 99%
“…This process can occur repeatedly, limited by the absolute number of charges and activation energy available [49]. Indeed, in favorable cases as many as seven successive dissociation steps have been observed [50].…”
Section: Collision-induced Dissociationmentioning
confidence: 99%
“…Furthermore, it was shown that capsid mutations can alter the mechanical strength of cowpea chlorotic mottle virus and minute virus of mice (25,26). Nanoindentation techniques have also been used to analyze the morphology of different capsids of one virus (e.g., the T ϭ 3 and T ϭ 4 hepatitis B capsids), which were shown to have mechanically similar shells (27).…”
mentioning
confidence: 99%
“…Analysis of large MDa complexes such as the ribosome 19 and highly ordered virus capsids [20][21][22] , in defining substrate binding to molecular machines [23][24][25] , or the characterization of subunit interaction networks 26,17,16,17,27,28 serve as but a few examples of the value of this approach.…”
Section: Discussionmentioning
confidence: 99%